Electrochemically Deposited rGO Cu2S Composite as a High-Performance Counter Electrode for Quantum Dot-Sensitized Solar Cells - Duyen, Nguyen Thuy Kieu; Hanh, Nguyen Thi My; Hieu, Le Van; Luu, Thi Viet Ha; Dang, Huu Phuc (Science and Technology Indonesia, 2026)
This study reports the development of reduced graphene oxide (rGO), copper sulfide (Cu2S), and their hybrid composite (rGO-Cu2S) as counter electrodes (CEs) for quantum dot-sensitized solar cells (QDSSCs). The electrodes were fabricated on FTO substrates via a simple, low-temperature electrochemical deposition method. Morphological analysis revealed flower-like Cu2S nanostructures and wrinkled rGO sheets, while the composite combined these features into a uniform hybrid layer. Electrochemical measurements demonstrated that the rGO-Cu2S CE exhibited superior catalytic activity and lower charge-transfer resistance compared to the individual materials. When integrated into QDSSCs, the rGO-Cu2S electrode achieved the highest power conversion efficiency (4.65%), outperforming Cu2S (3.77%) and rGO (3.24%). The synergistic interaction between conductive rGO networks and catalytically active Cu2S nanostructures underpin this improvement, highlighting rGO-Cu2S as a cost-effective and efficient alternative to noble-metal-based counter electrodes.